Sodium ion battery containing layered sodium oxide material and positive electrode sheet manufacturing process thereof

By doping niobium and antimony into the layered oxide positive electrode material and optimizing the treatment process, the problems of material stability and capacity attenuation are solved, and high cyclic stability and specific capacity are improved.

CN119153630BActive Publication Date: 2025-04-11ZHEJIANG GBS ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411667439.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-11
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

Laminated oxide positive electrode materials have poor stability in air, and capacity attenuation is prone to occur under long-term cycles and high current density, which affects its practical application.

Method used

Doping niobium (Nb) and antimony (Sb) elements in the precursor, and processing with a specific treatment solution, the residual alkali content on the surface of the layered sodium oxide material is reduced, and the process is optimized to improve the stability of the material.

Benefits of technology

It significantly improves the structural stability and electrochemical performance of layered oxide positive electrode materials, improves the cycle stability and specific capacity of sodium ion batteries, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion battery manufacturing, and specifically discloses a sodium ion battery containing a layered sodium oxide material and a positive electrode sheet manufacturing process thereof. The positive electrode sheet manufacturing process of the sodium ion battery is as follows: sodium carbonate, cobalt trioxide, nickel trioxide, ferric oxide, and D source metal oxide are mixed, then mixed with a functional additive and ball milled, dried, and a precursor material is obtained; the precursor material is tableted, roasted, cooled, and ground to obtain a layered sodium oxide material; the layered sodium oxide material is added to a treatment liquid I and stirred, allowed to stand, filtered, dried, and then sprayed with a treatment liquid II and stirred, dried, and ground to obtain a positive electrode material; the positive electrode material is mixed with a conductive agent and a binder, N-methylpyrrolidone is added, degassed, a positive electrode slurry is obtained, and then the positive electrode slurry is coated on an aluminum foil to make a positive electrode sheet. The sodium ion battery of the present invention has excellent cycle stability and high specific capacity, and the manufacturing process of the present invention is simple to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery manufacturing, and in particular relates to a sodium ion battery containing layered sodium oxide material and a positive electrode sheet manufacturing process thereof. Background Art

[0002] With the acceleration of the transformation of the global energy structure, energy storage technology has become one of the key factors in promoting the widespread application of clean energy. Among the many energy storage technologies, sodium-ion batteries have gradually become a hot spot for research and application due to their relatively low raw material costs and abundant sodium resource reserves. Especially in the context of limited lithium resources and large price fluctuations, sodium-ion batteries have shown significant cost advantages and broad application prospects. From a technical perspective, the core of sodium-ion batteries lies in their ability to store and release electrical energy through the reversible insertion and deintercalation of sodium ions between the positive and negative electrodes. The selection of positive electrode materials in this process is crucial to the overall performance of the battery and directly affects the energy density, cycle life and safety of the battery. At present, the research on positive electrode materials for sodium-ion batteries mainly focuses on several types of materials such as layered transition metal oxides, Prussian blue analogs, polyanion compounds and tunnel oxides.

[0003] Among them, layered transition metal oxides have become one of the most promising cathode materials due to their high theoretical specific capacity and good electrochemical performance. This type of material usually has good structural stability and high electronic conductivity, which can effectively promote the rapid transmission of sodium ions, thereby improving the charge and discharge efficiency and cycle stability of the battery. In addition, by means of element doping or surface modification of layered oxides, their electrochemical properties can be further optimized to meet the diverse requirements of battery performance in different application scenarios. Despite this, layered oxide cathode materials still face many challenges, including how to further improve the specific capacity of materials, reduce production costs, and improve the cycle stability of materials. Although sodium-ion batteries have obvious advantages over lithium-ion batteries in terms of cost and resources, there is still a certain gap in energy density. This is mainly because the larger radius of sodium ions leads to a slower diffusion rate in electrode materials, which affects the overall performance of the battery. Therefore, future research directions will focus more on the development of new cathode materials, especially materials that can provide higher specific capacity and better cycle stability, in order to gradually narrow the gap in energy density with lithium-ion batteries while maintaining cost advantages.

[0004] Chinese patent document CN111564605A discloses a layered oxide positive electrode and a preparation method and application thereof and a sodium ion battery containing the layered oxide positive electrode. The layered oxide positive electrode is prepared as follows: a sodium compound, a manganese compound and a compound formed by doping a metal element are mixed according to the proportion of the chemical formula, ball milled, calcined in stages under an oxygen atmosphere, and cooled to obtain the obtained compound; wherein the sodium compound is selected from one or more of sodium carbonate, sodium nitrate, sodium oxide, sodium peroxide or sodium hydroxide, the manganese compound is selected from one or more of manganese carbonate, manganese nitrate, manganese dioxide, manganese trioxide, and manganese hydroxide, and the doped metal element is selected from K, Ca, S r, Ba, Li, Mg, Zn or one or more; the sodium ion battery comprises the above-mentioned layered oxide positive electrode, negative electrode, electrolyte and separator, which are assembled by conventional methods in the art; the positive electrode material of the patent introduces doped metal ions into the alkali metal position of the alkali metal layer and the transition metal layer respectively, and its positive electrode can effectively improve the structural stability of the anion-participated layered oxide positive electrode during the cycle, and has a higher capacity and better cycle stability; however, the residual alkali content on the surface of the layered oxide is relatively high, and its cycle performance will gradually deteriorate with use, which has an adverse effect on the service life and storage stability of the sodium ion battery, and needs to be further improved and enhanced. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a sodium ion battery containing a layered sodium oxide material and a manufacturing process for a positive electrode sheet thereof. The present invention further improves the stability of the material by doping the layered oxide with specific rare metal elements and optimizing the process to reduce the residual alkali content on the surface of the layered sodium oxide material, so that the sodium ion battery has excellent cycle stability and high specific capacity.

[0006] The technical solution adopted by the present invention is:

[0007] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material, specifically comprising the following steps:

[0008] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, and a D source metal oxide to obtain an initial material; mixing the initial material with a functional additive, ball milling, and drying to obtain a precursor material; pressing the precursor material into a sheet, and then roasting, cooling, and grinding to obtain a layered sodium oxide material;

[0009] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring, standing, filtering, and drying to obtain a first-treated layered sodium oxide material; spraying the treatment solution II onto the first-treated layered sodium oxide material, stirring, drying, and grinding to obtain a positive electrode material;

[0010] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent and a binder, adding N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0011] As a preferred embodiment of the present invention, a process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0012] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, and D source metal oxide uniformly to obtain an initial material; adding the initial material and the functional additive into a ball mill, ball milling at 300-500 rpm for 2-4 hours, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets, then placing the sheet in a muffle furnace and heating to 800-900° C. and calcining for 10-15 hours, cooling to room temperature with the furnace, and grinding to obtain a layered sodium oxide material;

[0013] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 200-400 rpm for 5-20 min, then standing for 10-15 h, filtering, and vacuum drying to obtain a once-treated layered sodium oxide material; spraying the treatment solution II evenly onto the once-treated layered sodium oxide material, stirring at 700-900 rpm for 40-60 min, vacuum drying, and grinding to obtain a positive electrode material;

[0014] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent and a binder, adjusting the solid content to 38-42% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0015] Preferably, in step (1), the molar ratio of sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide and D source metal oxide is (10-11):(2-4):(2-4):(0.5-2):(2-4).

[0016] Preferably, the D source metal oxide is one or more of titanium dioxide, vanadium pentoxide, zirconium dioxide, niobium pentoxide, and antimony trioxide.

[0017] Preferably, the D source metal oxide is composed of niobium pentoxide and antimony trioxide in a molar ratio of 0.5-2:1.

[0018] In the study of positive electrode materials for sodium-ion batteries, layered oxides have attracted much attention due to their high theoretical specific capacity and good electrochemical properties. However, this type of material has poor stability in the air and is prone to capacity decay under long-term cycles and high current density, which limits its practical application. In order to solve this problem, the present invention improves the stability of layered oxides by adding metal oxides containing niobium (Nb) and antimony (Sb) to the precursor. First, the doping of niobium elements effectively enhances the structural stability of layered oxide materials. Niobium has a large atomic radius, and after doping, it can expand the lattice spacing, play a physical support effect, and prevent the layered oxide from structural collapse during long-term cycles. This increase in lattice spacing not only helps to maintain the structural integrity of the material, but also reduces the resistance to sodium ion transmission and improves the electrochemical activity of the material. Secondly, the introduction of antimony further enhances the stability of the material. As a p-block element, the electronic structure characteristics of antimony can adjust the electronic state of the material and improve its electronic conductivity. At the same time, the doping of antimony helps to form a more stable solid solution phase and reduce the occurrence of side reactions, thereby inhibiting the structural changes and performance degradation of the material during the charging and discharging process. The introduction of antimony can also improve the surface properties of the material, enhance its stability in the air, reduce the reaction with moisture and carbon dioxide in the environment, and further extend the service life of the material. The simultaneous doping of niobium and antimony further improves the structural stability and electrochemical properties of the layered oxide positive electrode material through the synergistic effect of the above-mentioned multiple mechanisms, which not only helps to maintain the capacity retention rate of the material in long-term cycles, but also improves its performance at high current density, providing more reliable technical support for the practical application of sodium-ion batteries.

[0019] Preferably, in step (1), the functional additive is composed of ethylene glycol and polyethyleneimine in a weight ratio of 3-5:1.

[0020] Preferably, in step (1), the amount of the functional additive is 1-2% of the weight of the initial material.

[0021] The present invention also adds a functional auxiliary agent composed of ethylene glycol and polyethylene imine during the preparation process of the layered oxide sodium material; first, during the ball milling process, the combination of polyethylene imine and ethylene glycol plays an important wetting and dispersing role. Polyethylene imine has good hydrophilicity and lipophilicity, and can be evenly covered on the surface of the raw material particles during ball milling, effectively preventing the agglomeration between the particles. It can effectively assist ethylene glycol, further enhance the dispersion effect of the raw materials, ensure that the components are fully mixed, so as to obtain particles with uniform particle size. This uniform mixing and dispersion not only helps to improve the crystallinity of the material, but also ensures the uniform distribution of the components in the subsequent roasting process. Second, during the roasting process, polyethylene imine plays a unique pore-forming role. At high temperature, polyethylene imine will decompose and produce gas. These gases form tiny bubbles inside the material, and finally form a porous structure. This porous structure significantly increases the surface area of ​​the material, providing more channels for the rapid transmission of sodium ions. The high specific surface area and porous structure are not only conducive to the embedding and de-embedding of sodium ions, but also can effectively improve the electrochemical activity of the material, thereby improving the rate performance and cycle stability of the battery. In addition, this porous structure also helps to inhibit the dissolution loss of active materials during the charge and discharge process; in traditional layered oxide materials, active materials are prone to dissolution during long-term cycles, resulting in capacity decay, and the formation of a porous structure can provide more physical barriers, effectively preventing the loss of active materials, thereby maintaining the structural stability and electrochemical properties of the material. In summary, by adding functional additives composed of ethylene glycol and polyethyleneimine during the preparation of layered sodium oxide materials, not only can the uniform mixing and dispersion of the raw materials be ensured, but also a porous structure can be formed during the calcination process, significantly increasing the specific surface area and pore volume of the material. These improvements not only help to improve the electrochemical properties of the material, but also effectively inhibit the dissolution loss of active materials, thereby significantly improving the cycle performance and overall stability of sodium-ion batteries.

[0022] Preferably, in step (2), the weight ratio of the treatment solution I to the layered sodium oxide material is 10:7-10.

[0023] Preferably, in step (2), the treatment solution I is composed of 13-17 wt % glycolic acid and the remainder 1,3-propylene glycol.

[0024] Preferably, in step (2), the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:8-10.

[0025] Preferably, in step (2), the treatment solution II is composed of 4-6 wt % sodium difluorophosphate, 43-46 wt % diethyl carbonate, and the balance propylene carbonate.

[0026] In the preparation process of positive electrode materials for sodium-ion batteries, layered oxide materials often face a key problem: the volatilization of sodium during high-temperature calcination. In order to compensate for this, the amount of sodium raw material is usually increased (more than 5%), but this will result in a small amount of sodium oxide remaining on the surface of the layered oxide finally prepared. These residual sodium oxides will adsorb water and carbon dioxide in the air to form residual alkalis such as sodium hydroxide and sodium carbonate. These residual alkalis will not only affect the processing properties of the material, but will also decompose during battery charging and discharging and high temperature, leading to flatulence, increasing irreversible capacity loss, and deteriorating the battery's cycle performance; in addition, unlike lithium battery positive electrode materials, the layered oxide materials of sodium-ion batteries cannot be directly washed with water (which will cause sodium ions to dissolve inside the material).

[0027] In order to solve this problem, the present invention uses a treatment solution I composed of glycolic acid and 1,3-propylene glycol, and a treatment solution II composed of sodium difluorophosphate, diethyl carbonate, and propylene carbonate to jointly treat the layered sodium oxide material. This method can significantly reduce the residual alkali content on the surface, improve the processing performance of the material, and improve the cycle stability and storage (heat resistance) stability of the sodium ion battery. The combined use of glycolic acid and 1,3-propylene glycol can effectively neutralize and remove the residual alkali on the surface, and 1,3-propylene glycol can help glycolic acid better penetrate into the residual alkali on the surface of the material; sodium difluorophosphate can act as a protective film on the surface of the material, and this film can effectively prevent moisture and carbon dioxide in the air from being adsorbed to the surface of the material again, thereby preventing the generation of residual alkali and enhancing the surface stability of the material; sodium difluorophosphate, diethyl carbonate, and propylene carbonate are used as solvents to help sodium difluorophosphate better disperse and improve its deposition efficiency on the surface of the material.

[0028] Preferably, in step (1), the pressure of the tablet press is 15-25 MPa.

[0029] Preferably, in step (1), the heating rate of the muffle furnace is 1-3°C / min.

[0030] Preferably, in step (1), the muffle furnace calcination atmosphere is oxygen or air.

[0031] Preferably, in step (1), the chemical formula of the layered sodium oxide material is Na n Co x Ni y Fe z D 1-x-y-z O2; where 0.8≤n≤1.0, 0.2 <x≤0.4,0.2<y≤0.4,0.1<z≤0.2。

[0032] Preferably, D is one or more of Ti, V, Zr, Nb and Sb.

[0033] Preferably, the D consists of Nb and Sb in a molar ratio of 0.5-2:1.

[0034] Preferably, in step (1), the chemical formula of the layered sodium oxide material is NaCo 0.3 Ni 0.3 Fe 0.1 Nb 0.15 Sb 0.15 O2.

[0035] Preferably, in step (3), the weight ratio of the positive electrode material to the conductive agent and the binder is (7-8):(0.4-0.6):(0.4-0.6).

[0036] Preferably, in step (3), the conductive agent is selected from one or a mixture of two or more of conductive carbon black, Ketjen black, acetylene black, conductive graphite, and carbon nanotubes.

[0037] Preferably, in step (3), the binder is selected from one or a mixture of two or more of polyvinylidene fluoride (PVDF), polyacrylic acid, and styrene-butadiene rubber.

[0038] The invention also discloses a sodium ion battery containing a layered sodium oxide material, including a positive electrode sheet manufactured by the above process.

[0039] Preferably, the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a sodium ion battery containing a layered sodium oxide material.

[0040] Preferably, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button battery in a vacuum glove box and packaged to obtain a sodium ion battery containing a layered sodium oxide material.

[0041] Preferably, in step (3), the electrolyte is 0.8-1.2 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of solvent EC:DMC:EMC is (1-2):(1-2):1),

[0042] Preferably, in step (3), the negative electrode sheet is a metallic sodium sheet.

[0043] Preferably, in step (3), the diaphragm is a glass fiber diaphragm.

[0044] Beneficial effects of the present invention:

[0045] The present invention provides a sodium ion battery containing a layered sodium oxide material and a manufacturing process for a positive electrode sheet thereof. The present invention dopes a specific rare metal element when preparing a layered oxide precursor, optimizes the processing process of the positive electrode material, reduces the residual alkali content on the surface of the layered sodium oxide material, further improves the stability of the material, and enables the sodium ion battery to have excellent cycle stability and high specific capacity. DETAILED DESCRIPTION

[0046] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Embodiment 1:

[0048] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0049] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and roasting it for 12 hours at a heating rate of 2°C / min, the roasting atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0050] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 minutes, standing for 12 hours, filtering, and vacuum drying to obtain a layered sodium oxide material treated once; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is composed of 15wt% ethanolic acid and the balance is 1,3-propylene glycol; the treatment solution II is evenly sprayed on the layered sodium oxide material treated once, stirred at 800 rpm for 50 minutes, vacuum dried, and ground to obtain a positive electrode material; the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:9; the treatment solution II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate and the balance is propylene carbonate;

[0051] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0052] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0053] Embodiment 2:

[0054] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0055] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide and niobium pentoxide in a molar ratio of 10.5:3:3:1:3 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and calcining it for 12 hours at a heating rate of 2°C / min, the calcining atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0056] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 minutes, standing for 12 hours, filtering, and vacuum drying to obtain a layered sodium oxide material treated once; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is composed of 15wt% ethanolic acid and the balance is 1,3-propylene glycol; the treatment solution II is evenly sprayed on the layered sodium oxide material treated once, stirred at 800 rpm for 50 minutes, vacuum dried, and ground to obtain a positive electrode material; the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:9; the treatment solution II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate and the balance is propylene carbonate;

[0057] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0058] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0059] Embodiment 3:

[0060] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0061] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide and antimony trioxide in a molar ratio of 10.5:3:3:1:3 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to be pressed into a thin sheet at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and calcining it for 12 hours at a heating rate of 2°C / min, the calcining atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0062] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 minutes, standing for 12 hours, filtering, and vacuum drying to obtain a layered sodium oxide material treated once; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is composed of 15wt% ethanolic acid and the balance is 1,3-propylene glycol; the treatment solution II is evenly sprayed on the layered sodium oxide material treated once, stirred at 800 rpm for 50 minutes, vacuum dried, and ground to obtain a positive electrode material; the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:9; the treatment solution II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate and the balance is propylene carbonate;

[0063] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0064] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0065] Embodiment 4:

[0066] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0067] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400 rpm, wherein the functional additive is ethylene glycol, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20 MPa, then placing the precursor material in a muffle furnace and heating to 850° C. and calcining for 12 hours at a heating rate of 2° C. / min, the calcining atmosphere is oxygen, cooling to room temperature with the furnace, grinding, and obtaining a layered sodium oxide material;

[0068] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 minutes, standing for 12 hours, filtering, and vacuum drying to obtain a layered sodium oxide material treated once; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is composed of 15wt% ethanolic acid and the balance is 1,3-propylene glycol; the treatment solution II is evenly sprayed on the layered sodium oxide material treated once, stirred at 800 rpm for 50 minutes, vacuum dried, and ground to obtain a positive electrode material; the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:9; the treatment solution II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate and the balance is propylene carbonate;

[0069] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0070] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0071] Embodiment 5:

[0072] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0073] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and roasting it for 12 hours at a heating rate of 2°C / min, the roasting atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0074] Step (2), spraying the treatment liquid II uniformly onto the layered sodium oxide material obtained in step (1), stirring at 800 rpm for 50 min, vacuum drying, and grinding to obtain a positive electrode material; the weight ratio of the treatment liquid II to the layered sodium oxide material is 1:9; the treatment liquid II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate, and the balance propylene carbonate;

[0075] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0076] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0077] Embodiment 6:

[0078] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0079] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and roasting it for 12 hours at a heating rate of 2°C / min, the roasting atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0080] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 min, then standing for 12 h, filtering, vacuum drying, and grinding to obtain a positive electrode material; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is composed of 15 wt% glycolic acid and the balance is 1,3-propylene glycol;

[0081] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0082] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0083] Embodiment 7:

[0084] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0085] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into thin sheets at a pressure of 20MPa, then placing it in a muffle furnace and heating it to 850°C and roasting it for 12 hours at a heating rate of 2°C / min, the roasting atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a layered sodium oxide material;

[0086] Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring at 300 rpm for 10 minutes, standing for 12 hours, filtering, and vacuum drying to obtain a layered sodium oxide material treated once; the weight ratio of the treatment solution I to the layered sodium oxide material is 10:8; the treatment solution I is 1,3-propylene glycol; the treatment solution II is evenly sprayed on the layered sodium oxide material treated once, stirred at 800 rpm for 50 minutes, vacuum dried, and ground to obtain a positive electrode material; the weight ratio of the treatment solution II to the layered sodium oxide material treated once is 1:9; the treatment solution II is composed of 5wt% sodium difluorophosphate, 45wt% diethyl carbonate and the balance propylene carbonate;

[0087] Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0088] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0089] Embodiment 8:

[0090] A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material comprises the following steps:

[0091] Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, niobium pentoxide and antimony trioxide in a molar ratio of 10.5:3:3:1:1.5:1.5 to obtain an initial material; adding the initial material and a functional additive into a ball mill, ball milling for 3 hours at 400 rpm, wherein the functional additive is composed of ethylene glycol and polyethyleneimine (weight average molecular weight 3000) in a weight ratio of 4:1, and the amount of the functional additive is 1.5% of the weight of the initial material, and vacuum drying to obtain a precursor material; placing the precursor material in a tablet press to press into a thin sheet at a pressure of 20 MPa, then placing it in a muffle furnace and heating it to 850° C. and roasting it for 12 hours at a heating rate of 2° C. / min, the roasting atmosphere is oxygen, cooling it to room temperature with the furnace, grinding it, and obtaining a positive electrode material;

[0092] Step (2), mixing the positive electrode material obtained in step (1) with a conductive agent (conductive carbon black) and a binder (polyvinylidene fluoride) in a weight ratio of 7.5:0.5:0.5, adjusting the solid content to 40% with N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet.

[0093] Furthermore, the positive electrode sheet prepared in this embodiment is applied to a sodium ion battery containing a layered sodium oxide material, wherein the negative electrode sheet of the sodium ion battery adopts a metallic sodium sheet, the electrolyte adopts 1 mol / L sodium hexafluorophosphate NaPF6 (the volume ratio of the solvent EC:DMC:EMC is 1:1:1), and the diaphragm adopts a glass fiber diaphragm. In a vacuum glove box, the battery shell, the positive electrode sheet, the negative electrode sheet, the electrolyte, the diaphragm, the spring sheet, and the gasket are assembled into a button-type 2032 battery and packaged to obtain the sodium ion battery containing the layered sodium oxide material.

[0094] Test Example 1:

[0095] The sodium ion battery prepared in the above embodiment was tested for charge and discharge performance at a current density of 1C = 240 mA / g and a test voltage range of 2.0-4.2 V, including the first cycle discharge capacity of the battery at a current density of 0.1C and the capacity retention rate after 300 cycles at 5C. The test results are shown in Table 1:

[0096] Table 1 Battery specific capacity and cycle performance test results

[0097]

[0098] Test Example 2:

[0099] At room temperature, charge the battery to 4.2V at a constant current of 0.5C, then charge it to 0.02C at a constant voltage of 4.2V, let it stand for 60 minutes, discharge the battery to 2.0V at a constant current of 0.5C, and record the initial discharge capacity. At room temperature, charge the battery to 4.2V at a constant current of 0.5C, then charge it to 0.02C at a constant voltage of 4.2V, let it stand for 60 minutes, place the battery in a 65±2℃ constant temperature box for 2 weeks and then take it out. After standing at room temperature for 60 minutes, discharge the battery to 2.0V at a constant current of 0.5C, and record the remaining capacity. The 65℃ storage capacity retention rate is expressed as the ratio of the remaining capacity to the initial discharge capacity. The test results are shown in Table 2:

[0100] Table 2 Battery storage stability test results

[0101]

[0102] From the test results in Table 1-2, it can be seen that the sodium ion battery containing layered sodium oxide materials of the present invention has a high specific capacity and beneficial cycle stability and storage stability, especially the performance of Example 1 is the best. Compared with Examples 2-4, Example 1 simultaneously doped niobium and antimony in the layered oxide, and through the synergistic effect of multiple mechanisms, further improved the structural stability and electrochemical performance of the layered oxide positive electrode material, which not only helps to maintain the capacity retention rate of the material in long-term cycles, but also improves its performance under high current density; and in the preparation process of the layered sodium oxide material, the functional additives composed of ethylene glycol and polyethyleneimine are added, which not only plays a wetting and dispersing role in the ball milling process, but also effectively assists ethylene glycol to further enhance the dispersion effect of the raw materials, ensuring that the components are fully mixed, thereby obtaining a uniform particle size. The particles of one, this uniform mixing and dispersion not only helps to improve the crystallinity of the material, but also ensures the uniform distribution of each component in the subsequent calcination process, and during the calcination process, polyethyleneimine plays a pore-forming role. At high temperature, polyethyleneimine will decompose and produce gas. These gases form tiny bubbles inside the material, and finally form a porous structure. This porous structure significantly increases the surface area of ​​the material, providing more channels for the rapid transmission of sodium ions. The high specific surface area and porous structure are not only conducive to the embedding and de-embedding of sodium ions, but also effectively improve the electrochemical activity of the material, thereby improving the rate performance and cycle stability of the battery. Compared with Examples 5-8, Example 1 uses a treatment solution I composed of glycolic acid and 1,3-propylene glycol, and a treatment solution II composed of sodium difluorophosphate, diethyl carbonate, and propylene carbonate to jointly treat the layered sodium oxide material. This method can significantly reduce the surface residual alkali content, improve the processing performance of the material, and improve the cycle stability and storage (heat resistance) stability of the sodium ion battery.

[0103] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material, characterized in that: The following steps are involved: Step (1), mixing sodium carbonate, cobalt trioxide, nickel trioxide, iron trioxide, and a D source metal oxide to obtain an initial material; mixing the initial material with a functional additive, ball milling, and drying to obtain a precursor material; pressing the precursor material into a thin sheet, and then roasting, cooling, and grinding to obtain a layered sodium oxide material; Step (2), adding the layered sodium oxide material obtained in step (1) to the treatment solution I, stirring, standing, filtering, and drying to obtain a first-treated layered sodium oxide material; spraying the treatment solution II onto the first-treated layered sodium oxide material, stirring, drying, and grinding to obtain a positive electrode material; Step (3), mixing the positive electrode material obtained in step (2) with a conductive agent and a binder, adding N-methylpyrrolidone, degassing, and obtaining a positive electrode slurry; coating the positive electrode slurry on an aluminum foil to prepare a positive electrode sheet; In step (1), the molar ratio of the sodium carbonate, cobalt sesquioxide, nickel sesquioxide, iron sesquioxide, and D-source metal oxide is (10 - 11):(2 - 4):(2 - 4):(0.5 - 2):(2 - 4); the D-source metal oxide is composed of niobium pentoxide and antimony trioxide in a molar ratio of 0.5:1 - 2:1; the functional additive is composed of ethylene glycol and polyethyleneimine in a weight ratio of 3:1 - 5:1; the chemical general formula of the layered sodium oxide material is Na n Co x Ni y Fe z D 1-x-y-z O2; wherein, 0.8 ≤ n ≤ 1.0, 0.2 < x ≤ 0.4, 0.2 < y ≤ 0.4, 0.1 < z ≤ 0.2; D is composed of Nb and Sb in a molar ratio of 0.5 - 2:1; In step (2), the treatment liquid I is composed of 13-17wt% ethanolic acid and the balance is 1,3-propylene glycol; the treatment liquid II is composed of 4-6wt% sodium difluorophosphate, 43-46wt% diethyl carbonate and the balance is propylene carbonate.

2. The process for manufacturing a positive electrode sheet of a sodium ion battery containing a layered sodium oxide material according to claim 1, characterized in that: In step (3), the conductive agent is selected from one or a mixture of two or more of conductive carbon black, conductive graphite, and carbon nanotubes; the binder is selected from one or a mixture of two or more of polyvinylidene fluoride PVDF, polyacrylic acid, and styrene-butadiene rubber.

3. A sodium ion battery containing a layered sodium oxide material, characterized in that: It comprises a positive electrode sheet manufactured by the process described in any one of claims 1-2.

Citation Information

Patent Citations

  • Layered oxide positive electrode, preparation method and application thereof and sodium-ion battery containing layered oxide positive electrode

    CN111564605A

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN114744172A

  • Method for reducing residual alkali on surface of sodium ion battery positive electrode material and application

    CN115995560A

  • Method for reducing content of residual alkali on surface of layered positive electrode material of sodium-ion battery, positive electrode material of sodium-ion battery and sodium-ion battery

    CN116495800A